The process of responding to graduate examinations in Accountancy colleges: Construct validation - Castañeda Figueiras, Sandra (2007)
The construct validity of six hypothesized dimensions was explored for an Accountancy majorgraduation examination, in order to understand the underlying process of responding. Using answers from 313 examinees to an intentional sample of 17 objective items administered on large scale, a confirmatory factorial analysis was carried out, with a Multi-Trait Multi-Method matrix (MTMM): Traits represented three cognitive operations required to solve the items and the methods represented three knowledge fields of the content. Each item was linked to a cog- nitive operation and to a knowledge field. The resulting model showed convergent validity in two constructs and its manifest variables and divergent only between technical and combined knowledge. Thus, the answering process was explained, simultaneously by the Understanding operation influenced by Theoretical knowledge. Implications to understanding the answering process in this type of examination through construct validation are discussed.